Traffic Flow Theory An introduction with exercises - L. Knoop, Victor (TU Delft Open, 2021)
Traffic processes cause several problems in the world. Traffic delay, pollution are some of it. They can be solved with the right road design or traffic management (control) measure. Before implementing these designs of measures, though, their effect could be tested. To this end, knowledge of traffic flow theory is needed.